Primary Neuroendocrine Carcinoma of Ocular Adnexa - Daisuke Yamanouchi; Toshiyuki Oshitari; Yosuke Nakamura; Jiro Yotsukura; Kaoru Asanagi; Takayuki Baba; Tomohiro Nizawa; Takashi Kishimoto; Yoko Yonemori; Satoshi Ota; Shuichi Yamamoto (Case Reports in Ophthalmological Medicine)
We present our findings in a case of primary neuroendocrine carcinoma (NEC) of the lacrimal gland and a case of primary Merkel cell carcinoma (MCC) of the eyelid. An 86-year-old man noticed a swelling of the left upper eyelid three months earlier. We performed excision biopsy and histopathological examination indicated that he had a primary NEC of the left lacrimal gland. He underwent chemotherapy followed by excision including the clinically visible margins and 50 Gy radiotherapy of the surgical margins. He had neither recurrence nor metastasis for 6 months since the last radiotherapy. An 80-year-old man noticed a nodule in the right upper eyelid and was referred to our hospital because the size was increasing rapidly. A complete surgical excision of the margins of the tumor was performed with histopathological confirmation of negative margins. The final diagnosis was a primary MCC of the right upper eyelid. After surgery, he underwent 50 Gy radiotherapy on the neck to prevent metastasis. No recurrence or metastasis was found for two years. Although primary NEC of the ocular adnexa is extremely rare, the tumor has high malignancy and readily metastasizes. Thus, combined therapy including surgery, radiotherapy, and/or chemotherapy is needed for complete management of NEC.